Utilization of alternating current methods for manufacture of selective absorbing coatings for heat collectors - Klochko, N.P.; Volkova, N.D.; Starikov, V.V.; Kopach, V.R.; Dobrotvorskaya, M.V.; Mateychenko, P.V.; Novikov, V.O. (Functional Materials, 2005)
Electrochemical processes, taking place during alternating current treatment of aluminum, and dependence of morphology, chemical composition and electrical properties of obtained surface on treatment regimes have been studied. The conditions, providing the formation of selectively absorbing Al/Al203 coating in hydrochloric acid solutions, have been determined. To improve the optical characteristics of such coatings we have elaborated an electrochemical alternating current deposition of cupric oxide on their surface in form of isolated CuО nanoparticles. The method is environmentally safe and does not require any re-equipment. It provides an enhanced spectral selectivity due to increase of sunlight absorption in visible spectral region without a significant emissivity increase in the infrared one. Изучены процессы, протекающие при электрохимической обработке алюминия переменным током. Исследована зависимость химического состава, морфологии и электрических свойств поверхности от режима обработки и определены условия, при которых в солянокислых растворах образуются селективные поглощающие покрытия Al/Al₂О₃. Для улучшения оптических характеристик таких покрытий разработан электрохимический переменнотоковый метод нанесения на их поверхность оксида меди в виде отдельных наночастиц CuО. Метод безопасен с экологической точки зрения, не требует замены технологической оснастки и приводит к увеличению спектральной селективности покрытий за счет роста коэффициента поглощения в видимой области спектра без заметного возрастания излучательной способности в инфракрасной области. Вивчено процеси, якi вiдбуваються протягом електрохiмiчної обробки алюмiнiю змiнним струмом. Дослiджено залежнiсть хiмiчного складу, морфологiї та електричних властивостей поверхонь вiд режимiв обробки i визначено умови, за яких в солянокислих розчинах можуть бути виготовленi селективнi поглинаючi покриття AI/AI₂O₃. 3 метою полiпшення оптичних властивостей таких покриттiв розроблено змiннострумовий електрохiмiчний метод нанесення на їх поверхню оксиду мiдi у формi окремих наночастинок CuО. Метод є безпечним з екологiчного погляду, не потребує замiни технологiчної оснастки i приводить до збiльшення спектральної селективностi покриттiв внаслiдок пiдвищення коефiцiєнта поглинання у видимiй частинi сонячного спектра без помiтного зростання здатностi до випромiнювання в iнфрачервонiй частинi.